On Properties of meromorphic solutions of difference PainlevÃ© I and II equation - Xue, Weimin; Teng, Yanmei (Global Journal of Mathematical Analysis, 2017)
In this paper, we investigate some properties of finite order transcendental meromorphic solutions of difference Painlev \(\)e\) I and II equations, and obtain precise estimations of exponents of convergence of poles of difference \(\)Δ w(z)=w(z+1)-w(z)\) and divided difference \(\)Δ w(z)w(z)\), and of fixed points of \(\)w(z+η) (ηC{0}\)).